KUALITAS PELAYANAN SPA PADA HOTEL DI KAWASAN WISATA NUSA DUA - I Gede Darmawijaya (Institut Pariwisata dan Bisnis Internasional, 2010)
Spa industry is a fast growing industry in the world. In Asia itself, it grew more than 100% from the year 2003 up to 2009, while in Indonesia, this industry grew 174%. This fenomenon brought beneficial effect to spa product industry, especially those companies that produce local or traditional spa product. In order to anticipate the needs and wants of spa industry’s customers to spa products, it is very imperative to reveal the quality of spa’s services viewed from the expectation and perception of international and domestic tourists.In relation to that reason, this study is conducted and aims to find out to what degree tourists perception towards the quality of spa’s services meet their expectations on it. This study was conducted purposively at five villas/resorts at tourist resort Nusa Dua, namely; Bali Desa, Kayu Manis Private Villas & Spa, The Laguna Resort & Spa, Melia Bali Villas & Spa Resort, and Inna Putri Bali. There are 224 respondents accidently used as samples. The data was collected by using questionnaire, then it was analysed with important and performance analysis. The findings of this study were the percentage of perception of tourists towards the quality of spa’s services that meets their expectation was 98.4%